2003
DOI: 10.1038/sj.bjc.6601383
|View full text |Cite
|
Sign up to set email alerts
|

Infertility rates following POMB/ACE chemotherapy for male and female germ cell tumours – a retrospective long-term follow-up study

Abstract: The risk of chemotherapy-induced infertility in male and female germ cell tumour (GCT) survivors is unclear, but may correlate with cisplatin dose. Here, we examine a large series of GCT patients for the effect of chemotherapy on those attempting to have children. Our GCT database was screened for nonseminomatous GCT patients who had (1) received POMB/ACE chemotherapy (cisplatin, vincristine, methotrexate, bleomycin alternating with actinomycin D, cyclophosphamide and etoposide) and (2) stage I male GCT patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“…Surgical strategies include conventional surgical resection or liver transplant. Salvage chemotherapeutic strategies do not work for every patient, and can result in long-term side effects, including severe hearing loss [44], infertility [45] and thinning of the heart wall [46].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical strategies include conventional surgical resection or liver transplant. Salvage chemotherapeutic strategies do not work for every patient, and can result in long-term side effects, including severe hearing loss [44], infertility [45] and thinning of the heart wall [46].…”
Section: Discussionmentioning
confidence: 99%
“…Perrin et al (29) demonstrated a pregnancy success rate of 7 of 29 (24%) in patients who had received chemotherapy and Bower et al (9) demonstrated a pregnancy rate of 14 of 33 (42%) following POMB/ACE chemotherapy, which are both comparable with our rate of 45%. A paper by Gaffan et al (30) looked at women who had fertility‐conserving surgery and then received chemotherapy and subsequently wanted to have a child, ie, excluded those who never tried. Of the 28 treated (POMB/ACE) women who attempted to have children, 25% (7/28) were unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
“…failed to find any evidence of reduced fertility in patients administered etoposide, methotrexate, actinomycin‐D, cyclophosphamide, and vincristine (EMA/CO regimen) for gestational trophoblastic tumors. A recent retrospective study by Gaffen and colleagues showed that the risk of infertility is low in both male and female germ cell tumor survivors taking 6‐mercaptopurine, vincristine, methotrexate, and prednisone / doxorubicin, cyclophosphamide, an etoposide (POMP/ACE regimen) 21 . Although the applied doses of MTX were not clearly mentioned, in a review it was reported that there is a 97% conception rate after the cessation of MTX treatment in women with gestational trophoblastic tumors 10 …”
Section: Discussionmentioning
confidence: 99%